High‐Mobility 2D Hole Gas at a SrTiO3 Interface. Issue 14 (27th February 2020) - Anh, Le Duc; Kaneta, Shingo; Tokunaga, Masashi; Seki, Munetoshi; Tabata, Hitoshi; Tanaka, Masaaki; Ohya, Shinobu
Abstract: Strontium titanate (SrTiO3 or STO) is important for oxide‐based electronics as it serves as a standard substrate for a wide range of high‐temperature superconducting cuprates, colossal magnetoresistive manganites, and multiferroics. Moreover, in its heterostructures with different materials, STO exhibits a broad spectrum of important physics such as superconductivity, magnetism, the quantum Hall effect, giant thermoelectric effect, and colossal ionic conductivity, most of which emerge in a two‐dimensional (2D) electron gas (2DEG) formed at an STO interface. However, little is known about its counterpart system, a 2D hole gas (2DHG) at the STO interface. Here, a simple way of realizing a 2DHG with an ultrahigh mobility of 24 000 cm 2 V −1 s −1 is demonstrated using an interface between STO and a thin amorphous FeO y layer, made by depositing a sub‐nanometer‐thick Fe layer on an STO substrate at room temperature. This mobility is the highest among those reported for holes in oxides. The carrier type can be switched from p‐type (2DHG) to n‐type (2DEG) by controlling the Fe thickness. This unprecedented method of forming a 2DHG at an STO interface provides a pathway to unexplored hole‐related physics in this system and enables extremely low‐cost and high‐speed oxide electronics. Abstract : By depositing a sub‐nanometer‐thick Fe layer on STO substrates at room temperature, a 2DHG with the highest hole mobility ever reported for oxides is realized at the STO interface. The carrier type can be switched from p‐type (2DHG) to n‐type (2DEG) by controlling the Fe thickness. These findings provide a pathway to extremely low‐cost and high‐speed oxide electronics.